Evaluation of pre induction scoring by clinical examination vs transvaginal sonography - Sharma, Sonali Kaur; Nagpal, Madhu; Thukral, CL (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to find out pre-induction cervical length by TV Sonography, determine Bishops score and to co-relate the obstetric outcome with these two variables. Methods: A study was done on 100 women with singleton pregnancies at 37-42 weeks of gestation, admitted for induction of labour in the Department of Obstetrics and Gynaecology at SGRDIMSR, Vallah, Amritsar, Punjab, India. All women underwent cervical assessment by both transvaginal ultrasound and Bishop Score and the outcome of labour induction was determined. Results: Of the 100 women, 53 women had vaginal delivery and 47 landed into LSCS. Bishop score < 6 and cervical length > 3 cm are cut off values of cervical unfavourablity. Successful induction was achieved among 87.5% and 78% women with favorable cervix according to Bishop Score and Cervical length respectively .Among the 92 and 50 women with unfavourable cervix according to Bishop score and cervical length, 48 (52.17%) and 14 (28%) had vaginal delivery respectively. Conclusions: Hence, cervical length by transvaginal ultrasound is a better predictor for the success of induction of labour as compared with assessment by Bishop Score alone.